Trends and issues in instructional design and technology - Reiser, Robert A.; Reiser, Robert A.; Dempsey, John V. (Boston : Pearson, 2012)
Trends and Issues in Instructional Design and Technology is intended to provide readers with a clear picture of the field of instructional design and technology, the trends and issues that have affected it in the past and present, and those trends and issues likely to affect it in the future. Professionals in the field need to be able to do more than just perform the skills associated with IDT. They need to be able to clearly describe the nature of the field, be familiar with the field's history and its current status, and be able to describe recent trends and issues that are having, or are likely to have, an impact on the field. The purpose of this book is to help readers attain these goals. - Publisher.
What Field Did You Say You Were In? Defining and Naming Our Field -- Characteristics of Instructional Design Models -- A History of Instructional Design and Technology -- Psychological Foundations of Instructional Design -- Constructivism in Practical and Historical Context -- The Learning Sciences: Where They Came From and What It Means For Instructional Designers -- Designing for Problem-Solving -- Instructional Theory and Technology for a Post-Industrial World -- Motivation, Volition, and Performance -- Evaluation in Instructional Design: A Comparison of Evaluation Models -- An Introduction to Return on Investment -- Managing On-Site and Virtual Design Teams -- Managing Scarce Resources in Training Organizations -- The Development and Evolution of Human Performance Improvement -- Performance Support -- Knowledge Management And Learning: Perfect Together -- Informal Learning -- Instructional Design in Business and Industry -- Instructional Design Opportunities in Military Education and Training Environments -- Performance, Instruction, and Technology in Health Care Education -- IDT in P-12 -- What Do Instructional Designers Do in Higher Education? A Written Symposium -- Developing Learning to Meet Complex Challenges for an Undivided World -- IDT in Asia -- IDT in Europe -- Getting an Instructional Design Position: Lessons From a Personal History -- Getting a Job in Business and Industry -- Professional Organizations and Publications in Instructional Design and Technology -- E-Learning and Instructional Design -- Reusability and Reusable Design -- Web 2.0 and Social Networking -- Using Rich Media Wisely -- Games and Learning -- Designing in Virtual Worlds -- Professional Ethics: Rules Applied to Practice -- Diversity and Accessibility -- The Changing Nature of Design -- Debate: The Benefits of Different Levels of Instructional Guidance.
Includes bibliographical references and index.
Keywords: Instructional systems -- Design; Educational technology